(untitled) (Journal of the College of Education for Women, 2019)
The deprivation Some of the children to exercise some fine motor activities a big problem , as a consequence, this problem plays of the delay in motor development during early childhood , Usually it happens to be the reasons for the lack of the right place to play , and the lack of the presence of the tools needed to play motor, or fear excessive protection by parents for their children as a result of lack of awareness of the importance of physical activity for the child to use his fingertips and fine his muscles . In addition to that small percentage of children spend most of their time in the daily activities and skills of non-motor , Such aswatching television, or play video games or they tend to play computer and mobile but they are moving away from sound methods in their dependence on fine motor skills when using the fingertips of their hand.The fine motor in kindergarten registration of such enormous developments in the control of the hands and fingers , This results in a lot of movements as in the ability to cut and paste and build homes using a small wooden or plastic pieces.The child at this stage attracted to different of motor games so you must make way for him to satisfy the wishes and his penchant for movement by practicing popular games in physical education lesson , Which helps to identify the shapes, colors and sizes, as well as that to develop his physical attitudes towards self-understanding and controlling his movements and compatibility between the eye and the hand, And working with his hands and feet and speed of response to external stimuli for cognitive mental processes in general growth , And help it to grow, which links between cognitive learning and cognitive growth, which is a prerequisite in social life, especially in the advanced ages.The current research aims to identify the fine motor skills of kindergarten children.In the current research was to adopt the point of view of complementarity when building test by defining fields, which included four fields , namely (manual - manual synergies , the circular motion of the hand and wrist , grab finger index finger and thumb, visual - manual synergies ).The researcher chose kindergarten (AL- Jamhoria), located in Morocco Street to apply tested on children preliminary stage whose age between (5-6) years totaling (190) boys and girls by (98) males and (92) females, divided into four divisions, so as to make the application Test them.In addition, the researcher to extract validity discrimination and difficulty and consistency of the test parameters, so that it can be applied to the sample. Having been testing the sample application, the researcher enter data obtained from children’s responses in statistical Pouch (SSPS), has revealed research that the sample suffer from weakness in the fine motor skills results, it has been interpreted researcher reasons for this weakness, according to this view integrative theories for the lack of attention to the motor side for these children since the early stages before entering kindergarten.